(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2019)
Today’s world is said to be vuca world i.e. volatile, uncertain, complex and ambiguous. This is reflected in all walks of life. Even the places where tender minds are being taken care of under a planned educational system, that is, schools, all the stakeholders are affected including teacher, the pivot of the school. Modern days schools in the society desperately need a concept of the common stress free ambience for getting happiness, the ultimate goal of life. Educationists want to increase the general happiness and commit to achieve that in the school system. School teachers who mainly deal with the tender mind of different age group children, are of paramount significance for the success of the educational endeavors. They play the key role in the grooming of child’s overall development. The ambience of happiness during the course of teaching learning process is the wonderful attribute that designs the sound outcome of the entire educational system .If the school teachers are in a state of happiness they can do the wonders in shaping a future happy citizen. This research paper has been prepared by the investigator to identify the characteristics of highly happy senior secondary school teachers in relation to the satisfaction with life and selected socio-educational variables on the basis of the analysis of the relevant data collected by administering appropriate tools on a sample of 271 Senior Secondary School teachers of Govt. aided and Unaided private (Public) Senior Secondary Schools of administrative District Central and District East under the Directorate of Education, GNCT Delhi.